2015
DOI: 10.2147/ijn.s92733
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced human bone marrow mesenchymal stem cell functions on cathodic arc plasma-treated titanium

Abstract: Surface modification of titanium for use in orthopedics has been explored for years; however, an ideal method of integrating titanium with native bone is still required to this day. Since human bone cells directly interact with nanostructured extracellular matrices, one of the most promising methods of improving titanium’s osseointegration involves inducing bio-mimetic nanotopography to enhance cell–implant interaction. In this regard, we explored an approach to functionalize the surface of titanium by deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The wide application of titanium (Ti) and its alloys as implants in oral implantology is due to such advantages as light mass, high specific strength, resistance to corrosion, low modulus of elasticity, and biocompatibility [ 1 ]. Although the success rate of titanium implants is high, 5%-10% of these implants still fails [ 2 , 3 ], mostly because of failed biocompatibility of the implants [ 4 , 5 ], which are influenced by surface properties of the implant [ 6 9 ]. It was reported that surface energy and wettability were two key factors that stimulated osteoblast response leading to osseointegration between bone and implant [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wide application of titanium (Ti) and its alloys as implants in oral implantology is due to such advantages as light mass, high specific strength, resistance to corrosion, low modulus of elasticity, and biocompatibility [ 1 ]. Although the success rate of titanium implants is high, 5%-10% of these implants still fails [ 2 , 3 ], mostly because of failed biocompatibility of the implants [ 4 , 5 ], which are influenced by surface properties of the implant [ 6 9 ]. It was reported that surface energy and wettability were two key factors that stimulated osteoblast response leading to osseointegration between bone and implant [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu tried to improve human bone marrow mesenchymal stem cell attachments and differentiation on implant treated surface. This treatment, called, plasma treatment, can be an ideal method of integrating titanium with native bone for orthopedic applications [23]. The nanostructured magnesium had effect on osteoblast function on a Weng 2013 study.…”
Section: Discussionmentioning
confidence: 99%
“…The poor early stability and insufficient stress conduction cannot afford a stabilized bonding between implants and the peripheral bone. Mechanical instability of the bone-implant interface will generate wear particles from any part of the implant 18,19 . Aluminum is one of biomaterials and wildly used for diagnostic, therapeutic material, and replacement for bone defect.…”
mentioning
confidence: 99%